Penerapan Metode Muroja’ah Dalam Menghafal Al-Qur’an - Rara Lauchia; Fazza Erwina Dwi; Mulyadi Ahmad (Yayasan Miftahul Ulum Sangatta Kutai Timur (KEP. MENKUMHAM RI No. AHU-0014779.AH.01.04.Tahun 2018) bekerjasama dengan Jurusan Tarbiyah STAI SANGATTA Kab. Kutai Timur., 2023)
Al-Qur'an is a guide to life for Muslims. Memorizing and reading the Qur'an is one of the suggestions commanded by Allah SWT to the people of the Prophet Muhammad SAW. For those who read one letter of the Qur'an, he will get 10 goodness. The purpose of this research is to find out the importance of learning the Koran, Fadhilah reading the Koran, the method of memorizing the Koran and the application of the muroja'ah method in memorizing the Koran. The method used in this research is the library research method. The result is that the application of the muroja'ah method in memorizing the Al-Qur'an is very easy to do so we are happy to memorize the Al-Qur'an. In this method, we not only memorize verses of the Qur'an, but we also know the contents of the verses of the Qur'an so that it is easier to implement in everyday life. In our opinion, this method is very helpful for those who want to memorize the Al-Qur'an so that it is easier, insha Allah.